Thermal Analysis and Improvements of the Power Battery Pack with Liquid Cooling for Electric Vehicles - Bizhong Xia; Yifan Liu; Rui Huang; Yadi Yang; Yongzhi Lai; Weiwei Zheng; Huawen Wang; Wei Wang; Mingwang Wang (Energies, 2019)
In order to ensure thermal safety and extended cycle life of Lithium-ion batteries (LIBs) used in electric vehicles (EVs), a typical thermal management scheme was proposed as a reference design for the power battery pack. Through the development of the model for theoretical analysis and numerical simulation combined with the thermal management test bench, the designed scheme could be evaluated. In particular, the three-dimensional transient thermal model was used as the type of model. The test result verified the accuracy and the rationality of the model, but it also showed that the reference design could not reach the qualified standard of thermal performance of the power battery pack. Based on the heat dissipation strategy of liquid cooling, a novel improved design solution was proposed. The results showed that the maximum temperature of the power battery pack dropped by 1 °C, and the temperature difference was reduced by 2 °C, which improved the thermal performance of the power battery pack and consequently provides guidance for the design of the battery thermal management system (BTMS).